Implementasi kurikulum merdeka pada sekolah penggerak dalam perspektif fungsi manajemen di sekolah dasar - Ratna Widya Irmayanti; Sri Marmoah; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2023)
The Merdeka Curriculum is the latest curriculum initiated by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). The curriculum is an important guideline in the learning process, especially the Merdeka Curriculum is a curriculum designed for post-pandemic learning recovery. The Merdeka Curriculum expects students to develop according to their abilities. Therefore, in the implementation of the Merdeka Curriculum, teachers are expected to be able to compile teaching modules that are in accordance with the needs and characteristics of students. The purpose of this research is to describe in detail the implementation of the merdeka curriculum in sekolah penggerak based on the perspective of the management function at SDN Kleco II. This study used a descriptive qualitative approach. The data source came from the principal and grade I and IV teachers of SDN Kleco II. Data collection techniques used in research are using questionnaires, observations, document analysis, and interviews. Data analysis using the Miles and Huberman model. The implementation of the merdeka curriculum in sekolah penggerak at SDN Kleco II from the perspective of the management function has gone through the stages of planning, organizing, actuating, and controlling properly.